Language and Gender: toward a Critical Feminist Linguistics - Sri Mulyani (Universitas Sanata Dharma, 2014)
This article attempts to map out the development of language and gender research and studies from its early stage to recent trend. The early language and gender research is inclined to essentialist view; and it subsequently changes its direction into a more non-essentialist perspective. Both essentialist and non-essentialist perspectives on language and gender research are not necessarily affiliated with feminist linguistics. Their research findings mostly conclude that womens language is inferior and women are not capable users of language. In a response to such sexist findings, various feminist scholars across the disciplines venture to rethink and redefine gender and language. Among many different approaches that they employ are two notable views, namely, the dominance and difference perspectives. One views man-woman differences in language use as a reflection of their power relation: the dominant and the subordinate. Meanwhile, the other sees this different linguistic use as a result of the different sub-cultures of their social environment (Coates, 2000: 413 and also Litosseliti, 2006:27). This shift toward a critical feminist linguistics is in fact informed by the current theories in critical thinking and feminist perspectives.Keywords: language, gender, feminist perspective